2016
DOI: 10.2147/ott.s97864
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise intervention in breast cancer survivors: a meta-analysis of 33 randomized controlled trails

Abstract: BackgroundExercise is associated with favorable outcomes in cancer survivors. The purpose of this meta-analysis is to comprehensively summarize the effects of exercise intervention in breast cancer survivors.MethodsA systematic search of PubMed, Elsevier, and Google scholar was conducted up to March 2015. References from relevant meta-analyses and reviews were also checked.ResultsThirty-three randomized controlled trials were included in this meta-analysis, including 2,659 breast cancer survivors. Compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 78 publications
4
103
3
3
Order By: Relevance
“…included. Moreover, the meta-analytic results are not consistent with the lack of effect on sleep outcomes in a more recent meta-analysis examining exercise effects on sleep in breast cancer survivors specifically due, in part, to few studies all enrolling small sample sizes (39). Of note, the data reported here are the first sleep outcomes data from a large randomized controlled physical activity (walking or traditional supervised aerobic exercise) and cancer trial specifically focused on post-primary treatment breast cancer survivors.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…included. Moreover, the meta-analytic results are not consistent with the lack of effect on sleep outcomes in a more recent meta-analysis examining exercise effects on sleep in breast cancer survivors specifically due, in part, to few studies all enrolling small sample sizes (39). Of note, the data reported here are the first sleep outcomes data from a large randomized controlled physical activity (walking or traditional supervised aerobic exercise) and cancer trial specifically focused on post-primary treatment breast cancer survivors.…”
Section: Discussionmentioning
confidence: 65%
“…Specifically, poor sleep is associated with greater breast cancer mortality (18,19) and being able to sleep is among the top 5 highest ranked patient-reported outcomes of importance (i.e., ranked as “important or very important” by 96% of breast cancer survivors) (13). Physical activity is one potential non-pharmacologic intervention for poor sleep quality (20,24) yet a recent meta-analysis reported no benefits of exercise interventions on sleep quality in breast cancer survivors (39). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity interventions also reduce depressive and anxiety symptoms in breast cancer survivors. 102 However, in a study of prostate cancer survivors in which depressive symptoms and anxiety were secondary outcomes, there was no effect of the physical activity intervention on mood. 103 …”
Section: Treatment Optionsmentioning
confidence: 99%
“…Furthermore, it has been reported that muscle-derived oncostatin M (OSM) and Irisin can decrease breast cancer cell viability, while SPARC inhibits tumorigenesis in the colon of exercising mice [115]. Herein, we have summarized the effects of physical exercise on other aspects of the body and overall health, such as inflammatory adipose tissue metabolism [103] sex hormones [116], leptin [102] and tumor factors [117], cardiopulmonary function [118][119][120], insulin resistance and sleep disorders [120], cachexia and lymphedema 2 , muscle mass and bone density [121], and genetic alteration [122] (Figure 1). …”
Section: Inflammatory Reactionsmentioning
confidence: 99%